Efektivitas Kampanye Vaksinasi Covid-19 Melalui Media Sosial di Kalangan Mahasiswa Ilmu Komunikasi Universitas Islam Negeri Sumatera Utara - Muhammad Iqbal; Indira Fatra Deni; Khoirul Jamil (Multiverse: Open Multidisciplinary Journal, 2023)
The aim of this research is to determine the effectiveness of the Covid-19 vaccination campaign through social media among Communication Science students of the State Islamic University of North Sumatra, where effectiveness includes opinions, attitudes, and behaviors. The theories used in this research are effectiveness, campaign, social media, and students as Generation Z. This research method utilizes a quantitative approach. The population in this research is Communication Science students of the State Islamic University of North Sumatra with a student registration number of 2019, totaling 146 individuals. The sample is determined using the Slovin formula, resulting in 59 respondents. The data collection technique in this research is a questionnaire, and data analysis is conducted using SPSS version 16.0. The research results indicate that the Covid-19 vaccination campaign through social media among Communication Science students of the State Islamic University of North Sumatra is considered effective.